2023
DOI: 10.3390/w15132488
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Irrigation Water Quality with Respect to the Reuse of Treated Wastewater in Al-Ahsa Oasis, Saudi Arabia

El-Sayed A. Badr,
Rady T. Tawfik,
Mortada S. Alomran

Abstract: Irrigation water quality is important to sustain agricultural productivity. The primary irrigation water sources in Al-Ahsa Oasis, KSA, are groundwater wells, mixed with treated wastewater and agricultural drainage. This study sought to evaluate irrigation water quality in Al-Ahsa Oasis with the aid of using irrigation water quality indices (IWQIs). One hundred and forty-eight different water samples were collected from various irrigation water resources throughout Al-Ahsa Oasis. The investigated physiochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Turbidity values ranged between 64 and 515 NTU in all the analyzed samples of LGW and were found to be very much higher than the maximum permissible value (5 NTU) for freshwater (IS10500, 2012). The hardness ranged between 160 and 376 mgL −1 and was observed sufficiently lower than the permissible value for drinking water (600 mgL −1 ) in the absence of an alternate source (Badr et al, 2023;IS10500, 2012).…”
Section: E X H I B I Tmentioning
confidence: 85%
“…Turbidity values ranged between 64 and 515 NTU in all the analyzed samples of LGW and were found to be very much higher than the maximum permissible value (5 NTU) for freshwater (IS10500, 2012). The hardness ranged between 160 and 376 mgL −1 and was observed sufficiently lower than the permissible value for drinking water (600 mgL −1 ) in the absence of an alternate source (Badr et al, 2023;IS10500, 2012).…”
Section: E X H I B I Tmentioning
confidence: 85%
“…Moreover, there was a strong correlation between each of the previously listed ions related to treated wastewater effluents. Furthermore, turbidity has an inverse relationship with organic variables such as TSS, COD, BOD 5 , and TOC, with correlation values that fluctuate from 0.85 to 0.77, 0.57, and 0.55 [ 32 ]. However, there are significant negative relationships between turbidity and sulfate.…”
Section: Resultsmentioning
confidence: 99%
“…The Ain Sefra WWTP was deemed appropriate for agricultural use, with nitrate levels below allowable limits, affirming efforts to prevent groundwater pollution. Badr et al [ 32 ] examined the quality of irrigation water in Al-Ahsa Oasis using 104 water samples. They discovered that treated wastewater combined with groundwater is suitable for irrigation with Higher levels of TDS, cations, and anions associated with spatial changes in water quality.…”
Section: Introductionmentioning
confidence: 99%
“…Permeability Index: The permeability index was determined to assess the risk of soil permeability (Badr et al, 2023). Throughout the study, an average value of PI was determined using Equation ( 4) and was found to be 51%, indicating that the wastewater sample is significant for continuous irrigation.…”
Section: Chloridementioning
confidence: 99%